2021
DOI: 10.18438/eblip29626
|View full text |Cite
|
Sign up to set email alerts
|

Library Anxiety Among Marginalized University Students in Northeast India

Abstract: Objective – Library anxiety experienced by students has been discussed extensively for many decades. While the phenomenon is widely recognized, little attention has been paid to seeing its specific effect on marginalized sections of the society. The study attempts to understand the library anxiety experienced by students at three different universities in Assam. Assam is the only state in Northeast India to have private, state, and central universities. These universities draw their student populations from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our findings in this study are consistent with the studies conducted by Abdoh (2021) andParsaei Mohammadi et al (2018). In contrast, Chutia and Nath (2021) and Gogoi et al (2021) presented different results in their studies, showing no difference in library anxiety levels among students from different universities.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our findings in this study are consistent with the studies conducted by Abdoh (2021) andParsaei Mohammadi et al (2018). In contrast, Chutia and Nath (2021) and Gogoi et al (2021) presented different results in their studies, showing no difference in library anxiety levels among students from different universities.…”
Section: Discussionmentioning
confidence: 88%
“…The International Journal of Information,Diversity,& Inclusion,8(2), 2024 ISSN 2574-3430, jps.library.utoronto.ca/index.php/ijidi/index DOI: 10.33137/ijidi.v8i2.42331 Gogoi et al (2021), Abdoh (2021), Parsaei Mohammadi et al (2018), and Noori et al (2017. These studies found no significant relationship between students' gender and their level of library anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation